2019
DOI: 10.2147/jir.s206800
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of maternal serum interleukin 17 in preeclampsia: diagnosis and prognosis</p>

Abstract: Background Immunological factors play a unique role in the setting of preeclampsia; there is a rising debate about the performance of interleukin 17 (IL-17) as inflammatory mediator in its pathogenesis. The purpose of this paper was to evaluate the significance of IL-17 in the diagnosis and prognosis of preeclampsia and estimate a cutoff value for better prediction. Methods A prospective case control study, 40 patient were enrolled in the study, two groups were designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…At the same time, lower than normal levels of transferrin (Chauhan et al, 2004) or the defects in its saturation ( 20 ) are commonly seen in children with ASD diagnosis ( 21 ). Similarly, levels of IL6, TNF-alpha, and IL17 are repeatedly reported as elevated in both PE and ASD [Kara et al, 2019; ( 22 27 )].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, lower than normal levels of transferrin (Chauhan et al, 2004) or the defects in its saturation ( 20 ) are commonly seen in children with ASD diagnosis ( 21 ). Similarly, levels of IL6, TNF-alpha, and IL17 are repeatedly reported as elevated in both PE and ASD [Kara et al, 2019; ( 22 27 )].…”
Section: Discussionmentioning
confidence: 99%
“…The 14-plex consisted of granulocyte-macrophage colony-stimulating factor (GM-CSF), IFN-γ, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12 (p70), IL-13, IL-17A, IL-23, and TNFα. This panel was selected because it contains cytokines that have been identified as part of the cytokine storm in response to severe SARS-CoV-2 infection [9], as well as cytokines that have been related to adverse pregnancy outcomes [26,27,28]. The assay sensitivities of these markers range from 0.11 -3.25 pg/mL.…”
Section: Multiplex Analysis Of Cytokinesmentioning
confidence: 99%
“…The clinical features of PE re ect widespread systemic in ammation [4]. A series of studies have found that the in ammatory cytokines increase because of trophoblast cells during the rst trimester of pregnancy, indicating that in ammatory cytokines play an important role in the development of PE [5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%